Computational fluid dynamics analysis of flow in diffuser of a desiccant type air dryer. (2021) - Sundararaj, S.; Antony Abraham, B.; Krishnakumar, P.
Abstract: In the present work numerical analysis of three dimensional flow behaviour in air dryer without diffuser and with diffuser is carried out using a standard Computational Fluid Dynamics (CFD) solver. The standard k - ε turbulent model is used in the study to predict the flow behaviour. The air dryer is investigated with diffusers including conical, annular, and curved wall configurations to analyse the distance from which desiccant contacts with air for better air drying. The operating conditions of air used for analysis are 0.0298 kg/s and 7 bar (gauge). The size of dryer considered for study are length 1150 mm, inlet diameter 20 mm, outlet diameter 26.4 mm, tower outer diameter 100 mm, and inner diameter 93.6 mm. The diffusers modelled and analysed are conical, annular and curved wall shape inlet diameter 20 mm, exit diameter 26.4 mm, and length 29 mm. The results show that air dryer with conical diffuser has the lowest velocity standard deviation compared with annular and curved wall configurations. Further analysis on conical diffuser with divergence angles from 9° to 47° in steps of 2° is carried and found that diffuser with 31° divergence angle shows minimum velocity standard deviation. The results reveal that the contact of air with desiccant starts at 250 mm from the inlet and the desiccant can be provided in the dryer from this location onwards.